Alternative reflectors for a compact sodium-cooled breed-and-burn fast reactor. (February 2015) - Hartanto, Donny; Kim, Yonghee
Highlights: A good neutron reflector is necessary in a small breed-and-burn fast reactor (B&BR) to improve the neutron economy. Impacts of various alternative reflectors on a sodium-cooled B&BR have been investigated from the neutronics perspectives. LME (lead–magnesium eutectic) and PbO are recommended as promising alternative reflector materials for the small B&BR. Abstract: The breed-and-burn fast reactor (B&BR) is a unique fast reactor concept that offers attractive characteristics in terms of core performance and non-proliferation aspects. The B&BR has the ability to breed its own fuel and use it in situ to achieve an extremely long life. In order to achieve the breed-and-burn condition, the neutron economy should be very good. In this work, a compact sodium-cooled B&BR is investigated from the physics point of view. In a compact size B&BR which usually has a higher neutron leakage, a good neutron reflector is essential to maintain the neutron economy. In the conventional sodium-cooled B&BRs, a steel reflector such as HT-9 is usually adopted as reflector material. In the current work, various alternative reflector materials such as pure lead, lead–bismuth eutectic (LBE), lead–magnesium eutectic (LME), PbO, MgO, Ni, and HT-9 are investigated from the neutronics perspectives. Several characterizations including the reflecting performance, core neutron spectrum, core leakage, power distribution, and sodium coolant void reactivity (CVR) have been performed to understand the behavior of each reflector material. The impact of the coarse lattice reflector configuration on the reflector performance and CVR has also been analyzed. In addition, the impact of the reflector material on the gas expansion module (GEM) worth has been investigated, too. Finally, it was concluded that lead-based reflectors such as LBE, LME, and PbO, are promising alternative reflector candidates for a compact B&BR. The calculations were all done by using a continuous energy Monte Carlo code.